Cover, Editorial Boards, Table of Contents - Andre Rachmat Scabra (Study Program of Aquaculture, Department of Fisheries and Marine Science, Faculty of Agriculture, University of Mataram, 2026)
Cover, Editorial Boards, Table of Contents